2021
DOI: 10.3389/fendo.2021.706964
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Enterovirus Infection and Type 1 Diabetes Risk: A Meta-Analysis of 38 Case-Control Studies

Abstract: ObjectiveThe association between enterovirus infection and type 1 diabetes (T1D) is controversial, and this meta-analysis aimed to explore the correlation.MethodsPubMed, Embase, Web of Science, and Cochrane Database were searched from inception to April 2020. Studies were included if they could provide sufficient information to calculate odds ratios and 95% confidence intervals. All analyses were performed using STATA 15.1.ResultsThirty-eight studies, encompassing 5921 subjects (2841 T1D patients and 3080 cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 64 publications
1
26
0
1
Order By: Relevance
“…In the adult cohort, we did not detect a correlation (p=0.79) between positivity for EV-RNA and type 1 diabetes, potentially due to the increased sensitivity of detection of EV-RNA in PBMC subsets. Overall, our findings are in line with the results of previous studies summarised in meta-analyses by Yeung et al and Wang et al [6,7], the majority of which reported increased detection of EV infection in individuals with autoimmunity and/or type 1 diabetes compared to those without. Given the 'snapshot' nature of this and previous studies [14,41] and the fact that EV viraemia lasts for only up to two weeks in peripheral blood [13], we suggest that larger study cohorts, longitudinal sampling, and improved sensitivity of viral detection (as shown here) are likely to be needed to reveal significant differences.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the adult cohort, we did not detect a correlation (p=0.79) between positivity for EV-RNA and type 1 diabetes, potentially due to the increased sensitivity of detection of EV-RNA in PBMC subsets. Overall, our findings are in line with the results of previous studies summarised in meta-analyses by Yeung et al and Wang et al [6,7], the majority of which reported increased detection of EV infection in individuals with autoimmunity and/or type 1 diabetes compared to those without. Given the 'snapshot' nature of this and previous studies [14,41] and the fact that EV viraemia lasts for only up to two weeks in peripheral blood [13], we suggest that larger study cohorts, longitudinal sampling, and improved sensitivity of viral detection (as shown here) are likely to be needed to reveal significant differences.…”
Section: Discussionsupporting
confidence: 93%
“…A prominent candidate environmental factor is virus infection [5], particularly infection with Coxsackievirus, a subgroup of the genus Enterovirus (EV) (Picornaviridae family) that has been extensively studied and linked to type 1 diabetes [6,7]. EV is detectable at a higher frequency in stool samples [8,9], pancreatic biopsies [10][11][12] and the peripheral blood [13,14] of individuals with type 1 diabetes compared to those without, while the presence of neutralising antibodies against Coxsackievirus correlates with beta cell autoimmunity [15].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological and clinical evidence in favour of enterovirus-associated pathogenesis of T1DM have been previously discussed and are based on findings in many parts of the world that enteroviral components (VP1 capsid protein and/or RNA) in serum, monocytes, gut mucosa and pancreas, and circulating anti-enterovirus immunoglobulins (IgM, IgG and IgA), are more frequently detected in patients with T1DM than in healthy individuals 11 , 19 , 39 41 . The significance of the association between the presence of enteroviral infection markers in various human biological samples and the risk of developing islet autoimmunity or T1DM was confirmed in Europe, Africa, Asia, Australia, North America and South America in two case–control meta-analyses of 24 and 38 studies including 4,448 and 5,921 participants, respectively 16 , 42 . The selective impairment of β-cells in T1DM is a consequence of a progressive and slow autoimmune process that can occur for several years before the onset of overt disease.…”
Section: Enterovirus Persistence In T1dmmentioning
confidence: 88%
“…Inflammatory cytokines‐induced incomplete autophagy makes the pancreatic β‐cells be sensitive to ER stress‐induced apoptosis, and GLP‐1 protects pancreatic β‐cells from death by restoring autophagic flux and increasing lysosomal function 28 . Human enterovirus infection has been associated with type I diabetes 186 . It is reported that incomplete autophagy enhances viral replication and production and impairs insulin secretion in E16‐infected INS(832/13) cells 187 …”
Section: Implications Of Incomplete Autophagy For Pharmacotherapymentioning
confidence: 99%
“…28 Human enterovirus infection has been associated with type I diabetes. 186 It is reported that incomplete autophagy enhances viral replication and production and impairs insulin secretion in E16-infected INS(832/13) cells. 187 In addition, glucolipotoxicity-induced incomplete autophagy is associated with lysosomal dysfunction-mediated the loss of β-cell mass, GLP-1 receptor agonist exendin-4 enhanced the autophagic flux by reversing the lysosomal dysfunction, and further improved β-cell survival.…”
Section: Diabetesmentioning
confidence: 99%